PENGARUH KEAKTIFAN ORGANISASI TERHADAP PRESTASI MAHASISWA - Alghifari Arya Renato; Dian Sudiantini, Aura Putri Amalia, Heffy Frisca Elisa, Izzati Maharani, Siti Rahmawati Janah (ADISAM PUBLISHER, 2024)
This research aims to measure the influence of activity in organizations on student academic achievement using quantitative methods and a survey approach. Data was collected through questionnaires distributed to 42 students active in various organizations on campus. The results of statistical analysis show that activeness in organizations has a significant positive relationship with student academic achievement, where this activeness helps in developing interpersonal skills, time management and leadership. However, it was also found that a good balance between organizational and academic activities is very important to avoid negative impacts on academic achievement. Support from educational institutions and effective time management skills are needed to achieve this balance, so that students can maximize the benefits of organizational activities while still achieving optimal academic achievement.